The relationship between orthostatic hypotension and cognitive impairment in Parkinson’s disease: a systematic review and meta-analysis - Liu, Yiping; Jiang, Yifan; Wang, Jingyi; Shi, Yan (Frontiers in Medicine, 2025)
ObjectiveOrthostatic hypotension (OH) and cognitive impairment are prevalent non-motor symptoms in Parkinson’s disease (PD). Although numerous epidemiological studies have explored the association between OH and cognitive impairment, the findings remain controversial. This study aims to systematically evaluate the relationship between OH and cognitive function in patients with PD and to investigate the impact of OH on different cognitive domains.MethodsDatabases, including the Chinese National Knowledge Infrastructure (CNKI), Wanfang Database, SinoMed, VIP (Database of Chinese Scientific and Technical Periodicals), PubMed, Embase, Cochrane Library, Web of Science, ProQuest, Scopus, and Ovid, were searched for eligible publications from their inception to July 2025. After literature screening and quality evaluation based on inclusion and exclusion criteria, meta-analysis, heterogeneity testing, sensitivity analysis, and subgroup analysis were conducted using Review Manager 5.4 software. Publication bias analysis was assessed using Stata software.ResultsThirteen studies with a total of 1,417 participants were ultimately included, comprising 552 Parkinson’s patients with OH (PD-OH group) and 865 Parkinson’s patients without OH (PD-NOH group). Compared to the PD-NOH group, the global cognitive score of the PD-OH group was significantly lower [SMD = −0.62, 95%CI [−0.78, −0.46], p < 0.01]. In terms of cognitive domains, the PD-OH group showed the following results: memory: SMD = −0.12, 95% CI (−0.64, 0.17), p = 0.25; executive function: SMD = −0.29, 95% CI (−0.50, −0.07), p < 0.01; verbal ability: SMD = −0.35, 95% CI (−0.65, −0.04), p < 0.01; attention: SMD = −0.12, 95% CI (−0.33, 0.09), p = 0.27; and visuospatial function; SMD = −0.40, 95% CI (−0.61, −0.18), p < 0.01. PD patients with OH did not exhibit significant cognitive impairment in the attention and memory domains but showed marked cognitive deficits in the executive function, verbal ability, and visuospatial function.ConclusionThis meta-analysis indicates that cognitive function decline in PD patients is associated with OH. Patients with OH have lower global cognitive scores compared to those without OH, particularly demonstrating significant deficits in executive, verbal, and visuospatial functions, especially in those with a long disease duration. Clinicians should be vigilant about these potential cognitive deficits and consider comprehensive cognitive assessments and targeted interventions for PD patients experiencing OH.